Adhesion properties of recycling greases - Grigorov, Andrey; Sytnik, Alexey; Karchakova, Valeriia; Ponomarenko, Vitaliy; Rudniev, Vasyl (My University, 2019)
The results of the study of the adhesion properties of recycling greases expressed in terms of the residual amount of grease that is stored on a metal plate after testing in a laboratory centrifuge are presented. It was established that the investigated samples of recycling greases in the range of the thickness of the deposition layer up to 1.0 mm, by their adhesion properties, are fully suitable for using in all types of bearings operated with a rotation speed of up to 2500 rpm. From the number of investigated grease samples, samples with a deposition layer thickness of 0.1 mm o have evidence of fairly high values of the rotational speed when the threshold value of the residual amount of grease is reached.
Keywords: recycling grease; adhesive properties; layer thickness; rotational speed; waste oil; centrifuge